Heritage Mission of Vilnius Temporary Archaeological Commission - Keršytė, Nastazija (Bibliotheca Lituana, 2012)
The heritage mission of Vilnius Temporary Archaeological Commission (1855–1865) is twofold. It strived to implement the Lithuanian cultural heritage continuum idea of “the past for the future” while performing a didactic task: to collect and publish historical documents and through the use of “Lithuanian antiquities” to organize the historical exposition of Vilnius Museum of Antiquities, creating conditions to recognize an objective history of Lithuania, in particular the period of Polish-Lithuanian union. Relying on 19th century positivistic attitudes this Commission sought for a position of an objective history observer, praising facts and proclaiming that the task of a historian is to show how it really was.Vilnius Temporary Archaeological Commission formed its position as the center for cultural heritage guardianship in the Northwester Krai of Imperial Russia. It regulated archeological excavations, performed scientific consulting and expertise functions, carried out archaeographical and museographical work. However it failed to organize systematic heritage accounting and protection of immovable heritage and sites of worth. Vilnius Temporary Archaeological Commission tried to draw public attention to a subdued nation’s need of an objective look at its land’s past and peculiarities, through the witnesses of its past – historical documents and musealias.
Keywords: none